Development and clinical usability of a new traction device “medical ring” for endoscopic submucosal dissection of early gastric cancer - Matsumoto, Kenshi (Springer US, 2013)
BACKGROUND: Although various traction devices exist for endoscopic submucosal dissection (ESD), the effects of the material used in the devices on the human body has not been considered. Moreover, there has been no report on a device that facilitates dissection both on the oral and anal side of the lesion. We made a traction device that has no deleterious effects on the body and is noninvasive, easy to use, and enables a bilateral approach in ESD. We report the process of its creation and a prospective evaluation of its usage in actual ESD procedures. METHODS: This study is prospective case control study. Thirty-seven patients for whom the device would be used were consecutively and prospectively enrolled (device used group). Control subjects in whom the device would not be used and who had lesions matched for size and location with those of the device used group were randomly selected (device not used group). Both groups were classified into three subgroups according to treatment difficulty: group A: easy; group B: intermediate; and group C: difficult. The dissection time per cm(2) in each group was examined. RESULTS: Dissection times in the device not used group/device used group were as follows: group A, 5.8/2.1 min/cm(2) (p < 0.01); group B, 6.1/3.8 min/cm(2) (p < 0.05); and group C, 7.9/3.6 min/cm(2) (p < 0.01), respectively. CONCLUSIONS: The newly developed medical ring was shown to be feasible and safe and allowed excellent visualization through suitable tension and facilitated rapid gastric ESD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00464-013-2887-6) contains supplementary material, which is available to authorized users.